Analytical and numerical study of the separation line between chip and work-piece during cutting processes. (1st January 2014) - Salvatore, F.; Mabrouki, T.; Hamdi, H.
In manufacturing industry, a high interest in analytical methods are usually researched because there are very practicable to use but those methods do not take into account all the aspects of the contact between the work material and the tool. In particular, ploughing and spring back are usually not considered, which is pertinent for small cutting edge radius but not for bigger ones (used tools). In reality, a part of the work-piece becomes chip and another part slides under the tool (elastic phenomena) and laterally (burrs). A separation line appears between those phenomena and the material under this surface stays in the work-piece during tool action. In this zone, elastic and plastic aspects induce temperature and spring back at the rear of the tool, which is important for residual stresses in the work-piece after cooling. In this paper, a simple analytical formulation is proposed in order to model the separation surface value. This analytical approach is fitted with 2D and 3D numerical simulations and verified with experimental forces and burr measurement.